Efficacy and Safety of Elective Switching from Intravenous to Subcutaneous Infliximab [CT-P13]: A Multicentre Cohort Study. (7th April 2022) - Smith, Philip J; Critchley, Lisa; Storey, Daniel; Gregg, Belle; Stenson, June; Kneebone, Andrew; Rimmer, Tracy; Burke, Stevena; Hussain, Shamas; Yi Teoh, Wan; Vazeille, Stephan; Serna, Solange; et al.
Abstract: Background: Intravenous [IV] infliximab is a well-established therapy for inflammatory bowel diseases [IBD] patients. A subcutaneous [SC] formulation of infliximab [CT-P13] has recently been shown to be as effective as IV infliximab after two doses of IV induction in a randomised trial, but there are no data to support elective switching of patients on maintenance IV infliximab therapy. We aimed to assess the effectiveness of an elective switching programme to SC CT-P13 in patients treated with IV infliximab. Methods: Patients on established maintenance IV infliximab, who switched to SC CT-P13, were included in this retrospective multicentre cohort study. Disease activity was monitored serially with the Harvey-Bradshaw Index [HBI] for Crohn's disease [CD] and the Simple Clinical Colitis Activity Index [SCCAI] for ulcerative colitis (UC) for up to 12 months at months 3, 6, and 12. Faecal calprotectin [FC] and C-reactive protein [CRP] were recorded at baseline and follow-up, if available. Infliximab trough levels were measured prior to switch and at months 3, 6, and 12 following switch. The primary outcome measure was treatment persistence at latest follow-up. Secondary outcome measures included infliximab pharmacokinetics [PK], safety, need for corticosteroid rescue therapy, and need for surgery. Results: We included 181 patients, of whom 115 [63.5%] had CD. The majority [72.4%] were on 8-weekly dosing of intravenous infliximab prior to switching, and more than half [59.1%] were on concomitant immunomodulatory therapy. The majority of patients (CD: 106, 92.2%; UC: 46, 76.7%; and IBD unclassified [IBD-U]: 5, 83.3%) were in clinical remission. Treatment persistence rate was high [ n = 167, 92.3%] and only 14 patients [7.7%] stopped treatment during the follow-up period. There was no significant difference between baseline and repeat measurements at 3, 6, or 12 months for HBI, SCCAI, CRP, or FC. Of the total cohort, 25 patients (13.8%) had perianal CD. Of these, only two patients [8%] had worsening of perianal CD and required antibiotic therapy and further examination under anaesthesia [EUA]. Both these patients also switched back to intravenous infliximab. Median infliximab level increased from a baseline of 8.9 µg/dl [range 0.4-16] to 16.0 µg/dl [range 2.3-16, p <0.001] at 3 months. Serum levels stayed stable at 6 months [median 16 µg/dl, range 0.3-17.2] and 12 months [median 16 µg/dl, range 0.3-19.1, both p <0.001 compared with baseline]. Among the variables examined, only antibodies to infliximab [ATI] was associated with infliximab levels (odds ratio [OR] -13.369, 95% CI -15.405, -11.333, p <0.001]. A total of 14 patients [7.7%] developed ATI; of these, nine [64.3%] were on concomitant immunomodulatory therapy. Immunomodulatory therapy was not significantly associated with development of ATI [ p = 0.15]. In a subset of patients receiving escalated IV infliximab dosing frequency prior to switching, no difference in treatment persistence was observed in patients receiving weekly versus alternate weekly SC CT-P13. Patient acceptance and satisfaction rates with SC CT-P13 were very high. Conclusions: Among patients on IV infliximab maintenance therapy switched to SC CT-P13, we observed high treatment persistence rates and low rates of immunogenicity, with no change in clinical disease activity indices or biomarkers. Infliximab levels increased after switch to SC CT-P13, and only ATI was associated with serum infliximab levels. Patient acceptance and satisfaction rates were high with SC CT-P13. Graphical Abstract: